Assessment of environmental tobacco smoke and respirable suspended particle exposures for nonsmokers in Lisbon by personal monitoring - Phillips, K.; Howard, D.A.; Bentley, M.C.; Alván, G. (Environment international, 1998)
One hundred and ninety seven randomly selected nonsmoking subjects collected air samples near their breathing zone by wearing personal monitors for 24-h. The study was centred in Lisbon, Portugal and comprised housewives in one group, primarily for assessing exposures in the home, and office workers in a second group to assess the contribution of the workplace to overall exposure. Samples collected were analysed for respirable suspended particles (RSP), nicotine, 3-ethenylpyridine and environmental tobacco smoke (ETS) particles using ultraviolet absorbance, fluorescence and solanesol measurements. Saliva cotinine analyses were also undertaken to confirm the nonsmoking status of the subjects. A large proportion of the data was below the limit of quantification and, apart from housewives from nonsmoking homes, there were few significant differences noticeable in 24-h time weighted average (TWA) concentrations between subject groups. Based on median TWA concentrations the highest exposed office workers encountered 43 μg m −3 RSP, 9.3 μg m −3 ETS particles and 0.58 μg m −3 nicotine. Overall the workplace contributed the most to nicotine and ETS particle exposure, whereas RSP exposure was higher away from the workplace. Annualised exposure estimates suggest that the most highly exposed subjects would receive approximately 20 cigarette equivalents per annum based upon upper decile levels.